Plate tectonics in the Phanerozoic - Kanasewich, E. R.; Havskov, J.; Evans, M. E. (Canadian Journal of Earth Sciences, 1978)
Paleomagnetic observations, oceanic magnetic lineations, and the present continental margins are combined in an interactive computer program to generate maps for seven periods in the Phanerozoic Era. The results are presented in the familiar Mercator projection and with less distortion on other projections. On an azimuthal-equidistant map projection with origin on the centroid of the continental lithosphere the boundaries display a high degree of symmetry and order. By using geological evidence on the position of geosynclines, volcanic assemblages, and zones of diastrophism an attempt is made to model a reconstruction of major plate boundaries in the past. During the Cambrian and Ordovician Periods the continental segments were as widely dispersed as at present and formed a ring of plates on the paleoequator but with North Africa and South America contiguous and close to the south pole. In these, as in other periods, there is symmetry about the spin axis. Extensive plate motion occurred at about the time of the Caledonian Orogeny when the continental segments evolved toward the formation of a single large group called Pangaea by Wegener. This evolution occupied much of the late Paleozoic and Mesozoic Eras. Toward the end of the Cretaceous Period a more dispersed form began to develop yielding the present pattern of two antipodal quasi-circular plates separated by a ring of more irregular quasi-elliptical plates. The results suggest the presence of a slowly evolving mantle-wide convection system that is symmetric about the Earth's spin axis. The dominant pattern during the late Paleozoic and the Cenozoic was of plates with dimensions of 60–120° in which the convective pattern may be described in terms of spherical harmonics of the third order. In the Mesozoic and late Paleozoic the plate sizes were of the order of 90–180° and physical parameters describing convection were presumably dominated by second order terms.